Climate Perception, Migration and Productivity of Maize Farmers in Ghana - Azumah, Shaibu Baanni; Mahama, Abass; Yegbemey, Rosaine N.; Dapilah, Frederick (Journal of Agricultural Studies, 2022)
High temperature, erratic rainfall, and drought are the three major physical manifestations of climate change in Ghana. Smallholder farmers in Ghana have shown vulnerability to the impacts of climate change, with some farmers employing migration as an adaptation mechanism. Using primary data collected from 500 maize farmers in seven districts of Ghana, our study draws a link among climate perception, migration and productivity of maize farmers by estimating a two-step Heckman sample selection model and employing inductive coding to analyse the qualitative data. The results show that farmers’ experience, access to farm credit, farm size, location, usage of NPK fertilizer, and local seeds have positive impact on the productivity of maize farmers. Additionally, household size, main occupation, membership in farmer-based organisations, and perception of declined soil fertility have significant effects on migration decisions of smallholder maize farmers. The qualitative reports show that perceived increase in temperature, drought, flooding, and erratic rainfall has led to a decline in the productivity of maize farmers. Among others, we recommend that relevant stakeholders (i.e., policy makers and NGOs in the agricultural space) should focus on promoting the use of improved seeds, and NKP fertilizer, coupled with the provision of farm credit and expansion of farm sizes to enhance the productivity of maize farmers in Ghana. Also, smallholder farmers should be supported to engage in alternative livelihood enterprises, join farmer-based organisations and to adopt techniques that enhance soil fertility in order to reduce climate-induced migration among maize farmers.